Comparison between Rocuronium and Atracurium Effect on Blood Pressure during General Anaesthesia in Baghdad Hospital - Adel Amen Hama; Noor Faris Hoobi; Sara Emad Majeed (Journal of Techniques)
This study was aimed to assess the blood pressure influence of rocuronium drug under general anesthesia and compares it with atracurium drug. The study recruited 50 adult patients, divided in to two groups the rocuronium drug groups which included 25 patients and atracurium drug group which included 25 patients, age ranged from (18-60 years) of both sexes who were (ASAI and ASAII) patients undergoing (elective surgeries) in Baghdad education hospital during the period from (October 2019 to March 2020). Anesthesia was induced with using I.V. propofol drug (1.5-2.5 mg/kg), ketamine drug (0.5 mg/kg) or (2-3 mg/kg) propofol drug.  For the endotreacheal tube, and facility of intubation injection muscle relaxation the rocuronium drug (0.6 mg/kg) or atracurium drug (0.5 mg/kg), for maintenance rocuronium drug (0.1-0.2 mg/kg). 60 sec. was used after administration of the relaxant, attempt of intubation. Next intubation, lungs were mechanically ventilated, monitored, blood pressure recorded and MAP after five minutes and every five minute for 15 minutes. The resulting P-value of MAP in Rocuronium drug groups and Atracuruim drug group at pre-operative was 0.811 which was non-significant (P> 0.05). While at induction it was 0.309 which was also non-significant (P> 0.05). After 1min it was 0.574 which was non-significant (P> 0.05). After 5min it was 0.321 which was non-significant. After 10 min it was 0.954 which was non-significant (P> 0.05). The blood pressure effected from rocuronium drug and atracurium drug are different under general anesthesia. The Atracurium drugs has less marked change in MAP. In healthy patients it maybe not be of importance, nevertheless it could be nonessential in patients with preexisting cerebral, cardiac diseases, hypertension or the elderly, but Rocuronium drug has a marked change in MAP. This could be cautiously in the patients with preexisting cardiac or cerebral pathology or elderly or hypertension. In conclusions the MAP was increased at induction of rocuronium drug and was decreased at induction of atracurium drug in this study.